Characteristics of polypharmacy in nonagenarians and centenarians - Viviane Maura Rubert; Rafaela Gageiro Luchesi Soares; Fernanda Mambrini Só e Silva; Isabella Knorr Velho; Maria Cristina Werlang; Tammy Shults; Jennifer Vann; Angelo Jose Bos (Instituto Nacional de Assistência Farmacêutica e Farmacoeconomia, 2023)
Introduction: Nonagenarians and centenarians are often affected by multiple morbidities that require the concomitant use of several drugs. Polypharmacy is defined as the consumption of five or more drugs and poses a cautionary challenge in healthcare. It is important to ensure the correct and safe use of medications. Objectives: To study the sociodemographic and clinical characteristics of polypharmacy in nonagenarians and centenarians. Methods: The location of the descriptive, cross-sectional, retrospective study was in the capital of the southern region of Brazil. A total of 243 nonagenarians and centenarians were evaluated between June 2016 to November 2016. Results: A total of 1450 medications were identified, corresponding to 5.9 ±2.87 medications per participant. Among the participants, 163 (67%) were considered as polypharmacy. The frequency of polypharmacy was higher than most reports in the literature, related to poor vision (74.18%, p=0.025), a history of cardiovascular diseases (78.00%, p<0.001), gastric diseases (77.33%, p=0.023), anxiety (80.00%, p=0.041), respiratory diseases (83.33%, p=0.014), arthrosis (76.53, p=0.010), thyroid disease (82.00%, p=0.012), symptoms of xerostomia (75.65%, p=0.008), dyspnea (78.85%, p=0.042), wheezing (81.10%, p=0.049), and fear of falling (72.90%, p=0.049). Conclusion: We concluded that polypharmacy is a prevalent phenomenon among nonagenarians and centenarians; importance of sociodemographic and clinical characteristics must be taken into consideration when providing primary healthcare to this population.